Analysis of the Influence and Impact of Using Financial Technology on Shopee Pay and Gopay Applications among Students - Bayu Septiadi; Habibulloh Siregar; Kadek Indra Daniawan (Prosiding International conference on Information Technology and Business (ICITB), 2022)
Technological developments in the industrial era 4.0 make patterns of consumer change through the use of digital technology, namely non-cash transactions called digital payments into new Financial Technology (FinTech) innovations in industrial era 4.0. Financial Technology (FinTech) is a financial service using technology that aims to facilitate users to make transactions digitally. Financial Technology (FinTech) has a very popular product, namely E-Wallet. The EWallet can allow someone to store funds digitally and make transactions online. Some applications that are included in the type of Financial Technology (FinTech) are Shopee Pay and Gopay. This study aims to determine the influence and impact of using Financial Technology (FinTech) on the Shopee Pay and Gopay applications among students. The method used in this research is a descriptive quantitative method based on the answers to questionnaires given to respondents. Respondents in this study were 81 students who used the Shopee Pay and Gopay applications.Keywords: Financial Technology, E-Wallet, Shopee Pay dan Gopay